Comparative analysis of toppling behaviour at Chuquicamata open-pit mine, Chile - M. Board; E. Chacon; P. Varona; L. Lorig (The Institute of Materials, Minerals and Mining, 1996)
Geomechanical factors at the mine are important and will become even more relevant as the pit expands and deepens. To address these demands a team was assembled to collect geomechanical information and perform numerical analysis. The west wall is the largest and flattest of all the design sectors in the pit and rigorous studies were carried out on this wall. The wall behaviour is controlled mainly by a set of steeply dipping joints within the slope in the Fortuna Granodiorite and a weak zone, the Zona Plastica, that extends vertically near the pit bottom. These features lead to large toppling displacements in the upper portions of the wall. Two numerical models were used to reproduce the general features of failure observed in the wall. The modelling indicated that a toppling mode of failure results from shear on the steeply dipping joints. The toppling leads to slumping or landslides whereby the west wall flows slowly downslope as the Zona Plastica compresses